2019
DOI: 10.12707/riv19037
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an empowerment-based educational program in self-efficacy perception in patients with diabetes

Abstract: Background: Studies suggest that empowerment-based educational models, implemented in patients with diabetes, may encourage the improvement of perceived self-efficacy. This variable is considered relevant in the therapeutic regimen self-management. Objectives: To evaluate the effectiveness of an empowerment-based educational program in patients with type 2 diabetes mellitus. Methodology: A quasi-experimental study, with two different evaluation moments, with a 6-week interval. A randomized sample of 42 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Of 39 included studies, 32 (85%) were RCTs [ 19 , 21 , 37 , 38 , 41 , 43 , 45 , 46 , 49 , 52 54 , 57 64 , 66 , 68 71 , 74 80 ]. Seven studies used other methods including five quasi-randomized trials, [ 39 , 56 , 65 , 72 , 73 ] one pre-post design, [ 51 ] and one partially randomized patient preference trial [ 48 ]. All studies were published in English within the 5-year period spanning 2016–2020, inclusive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 39 included studies, 32 (85%) were RCTs [ 19 , 21 , 37 , 38 , 41 , 43 , 45 , 46 , 49 , 52 54 , 57 64 , 66 , 68 71 , 74 80 ]. Seven studies used other methods including five quasi-randomized trials, [ 39 , 56 , 65 , 72 , 73 ] one pre-post design, [ 51 ] and one partially randomized patient preference trial [ 48 ]. All studies were published in English within the 5-year period spanning 2016–2020, inclusive.…”
Section: Resultsmentioning
confidence: 99%
“… Akturan et al 2017 [ 38 ] X 4: Therapeutic interview techniques by doctor 1 3. Almeida et al 2019 [ 39 ] X X 1: Modul 2: How diabetes affects my daily life 3: Decision making and daily problem-solving skills 2 4. Aslani et al 2019 [ 41 ] X?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational programs conducted in patients with other chronic conditions have also shown the significant potential to improve their lives. A study conducted by Almeida et al 19 found that participants who received an educational intervention compared to the group that received only conventional care had better self-care outcomes in managing the therapeutic regimen. 21 When patients know their perceptions of the disease, it is possible to understand how the condition influenced their life and emotions and how misconceptions can be addressed in tailored educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…But, in addition to encouraging knowledge acquisition, it is necessary to motivate individuals about their self‐efficacy. Feeling confident in one's knowledge is an important motivator for the adherence to healthy habits and behavior modification (Almeida et al., 2019; Lee et al., 2019). This confidence or self‐efficacy is individual's belief in himself and his ability to perform a given activity successfully (Fontes & Azzi, 2012).…”
Section: Introductionmentioning
confidence: 99%